PENGEMBANGAN MODUL ELEKTRONIK MATA KULIAH DESAIN GRAFIS PADA PROGRAM STUDI PENDIDIKAN TIK - Nurbani Nurbani; Sri Koriaty (Jurnal Teknologi Informasi dan Pendidikan, 2019)
This study aims to: 1) Produce the Electrocnik Graphic Design module in the P.TIK Study Program, IKIP PGRI Pontianak. 2) Knowing the student's feasibility and response to the Graphic Design electronic module. The research method used in this study is research and development. The research design used the Borg and Gall model. This research variable uses a single variable, namely the development of an electronic module in the Graphic Design course. The object of this study was the second semester students of the ICT Study Program IKIP-PGRI Pontianak 2017/2018. The results of the evaluation of the electronic module by the expert lecturer of the material obtained a score of 102.5 with eligibility criteria and the results of the evaluation of the electronic module by the media expert lecturer obtained a score of 94.5 with eligibility criteria .. While the response of students to electronic modules in a sample trial of 53 students obtained an average score of questionnaire 4 with good criteria. Based on these data it can be concluded that the electronic module application of graphic design developed is feasible and is good to use in the learning process